Pengaruh Lokasi Usaha Terhadap Pendapatan Pedagang Paguyuban Wirausaha Cilegon (Pawon) dalam Cilegon Car Free Day - Siska Mardiana; Annisarizki Annisarizki (FEB Universitas Sultan Ageng Tirtayasa, 2017)
UMKM sector plays an important role in the economy, and one of the forms of entrepreneurship in Cilegon today is the activity of Cilegon Car Free Day. Cilegon Car Free Day is a program established by the City Government of Cilegon by integrating morning sports activities and buying and selling activities that work with Paguyuban Wirausaha Cilegon (Pawon) as a manager under the protection of the Office of Industry, Trade and Cooperatives Cilegon City. The purpose of this study is to know whether the location of the business has an effect on the income of traders Paguyuban Wirausaha Cilegon (Pawon) traders in Cilegon Car Free Day The approach used is quantitative approach with the total population of 400 traders then by using slovin formula, resulting in a sample of 80 respondent. Analysis using linear regression analysis with variable X1 that is business location and variable Y that is merchant's income. The result of this research is business location has effect on the merchant's income of 36,7%